Does the Impact of Intensive Lifestyle Intervention on Cardiovascular Disease Risk Vary According to Frailty as Measured via Deficit Accumulation?. (20th June 2020) - Simpson, Felicia R; Pajewski, Nicholas M; Beavers, Kristen M; Kritchevsky, Stephen; McCaffery, Jeanne; Nicklas, Barbara J; Wing, Rena R; Bertoni, Alain; Ingram, Frank; Ojeranti, Daniel; Espeland, Mark A
Abstract: Background: Individuals are often counseled to use behavioral weight loss strategies to reduce risk for cardiovascular disease (CVD). We examined whether any benefits for CVD risk from weight loss intervention extend uniformly to individuals across a range of underlying health states. Methods: The time until first occurrence of a composite of fatal and nonfatal myocardial infarction and stroke, hospitalized angina, or CVD death was analyzed from 8 to 11 years of follow-up of 4, 859 adults who were overweight or obese, aged 45–76 years with Type 2 diabetes. Individuals had been randomly assigned to either an intensive lifestyle intervention (ILI) or diabetes support and education (DSE). Participants were grouped by intervention assignment and a frailty index (FI) based on deficit accumulation, ordered from fewer (first tertile) to more (third tertile) deficits. Results: Baseline FI scores were unrelated to intervention-induced weight losses and increased physical activity. The relative effectiveness of ILI on CVD incidence was inversely related to baseline FI in a graded fashion ( p = .01), with relative benefit (hazard ratio = 0.73 [95% CI 0.55, 0.98]) for individuals in the first FI tertile to no benefit (hazard ratio = 1.15 [0.94, 1.42]) among those in the third FI tertile. This graded relationship was not seen for individuals ordered by age tertile ( p = .52), and was stronger among participants aged 45–59 years (three-way interaction p = .04). Conclusions: In overweight/obese adults with diabetes, multidomain lifestyle interventions may be most effective in reducing CVD if administered before individuals have accrued many age-related health deficits. However, these exploratory analyses require confirmation by other studies. Clinical Trial Registration: NCT00017953